2016
DOI: 10.1021/acsami.6b11800
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Synthesis of Highly Dispersed PtCu Nanoparticles on Three-Dimensional Nitrogen-Doped Graphene Networks with Remarkably Enhanced Methanol Electrooxidation

Abstract: A well-dispersed PtCu alloy nanoparticles (NPs) on three-dimensional nitrogen-doped graphene (PtCu/3D N-G) electrocatalyst has been successfully synthesized by a conventional hydrothermal method combined with a high-efficiency microwave-assisted polyol process. The morphology, composition, and structures are well-characterized by scanning electron microscopy, transmission electron microscopy, Raman spectroscopy, X-ray powder diffraction, and X-ray photoelectron spectroscopy. Cyclic voltammograms illustrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(32 citation statements)
references
References 68 publications
1
31
0
Order By: Relevance
“…The importance of support has been increasingly recognized in the decades following the discovery of SMSIs (Garin, 2001 ; Diebold, 2003 ; Neophytides et al, 2005 ; Fu and Wagner, 2007 ; Liu et al, 2013 ). In addition to dispersing metallic particles, the support also functions to influence the catalytic properties of the supported metal catalysts through geometric or electronic effects (Naito et al, 2006 ; Krstajić et al, 2008 ; Delgado et al, 2011 ; Li et al, 2015 ). In this section, the mechanisms by which SMSI effects provide catalytic characteristics of supported catalysts for the RWGSR are further elucidated.…”
Section: Catalytic Systemmentioning
confidence: 99%
“…The importance of support has been increasingly recognized in the decades following the discovery of SMSIs (Garin, 2001 ; Diebold, 2003 ; Neophytides et al, 2005 ; Fu and Wagner, 2007 ; Liu et al, 2013 ). In addition to dispersing metallic particles, the support also functions to influence the catalytic properties of the supported metal catalysts through geometric or electronic effects (Naito et al, 2006 ; Krstajić et al, 2008 ; Delgado et al, 2011 ; Li et al, 2015 ). In this section, the mechanisms by which SMSI effects provide catalytic characteristics of supported catalysts for the RWGSR are further elucidated.…”
Section: Catalytic Systemmentioning
confidence: 99%
“…This fact indicated that the nitrogen atoms were successfully doped in the HCH to replace the carbon atoms at the inside and edges of the graphitic carbon layers. Pyridinic N and graphite N can be regarded as provider of active sites for nanomaterials nucleation and inhibit metal nanoparticles aggregation and diffusion [14]. In can be seen from Table 2, the PtSn/HCH-N0.2 with the lowest urea content shows a dominant pyrrolic-N, with a relative small ratio of pyridinic-N and Quaternery-N. With the content of urea increasing, the content of pyrrolic-N decreased, whereas the content of pyridinic-N and graphite N increased first and then decreased, they both reached the maximum for the PtSn/HCH-N0.5 catalyst.…”
Section: Xps Analysismentioning
confidence: 99%
“…Moreover, catalyst's performance is partly determined by the properties of support and interaction between support and metal nanoparticles, therefore, it is neccessary to develope an appropriate supporting material to enhance the performance of the catalysts. In recent years, the different morphology and structure carbon-based materials, such as carbon nanofiber [12], carbon sheet [13], graphene [14], carbon nanotubes [15], mesoporous carbon [16] and hollow carbon spheres [17] have been synthesized due to their large surface area, chemically inertia, high electronic conductivity and low cost. They have been investigated for many applications such as supercapacitors [16], lithium ion battery [18] and catalyst support [13] etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sluggish kinetics of oxygen reduction reaction (ORR) and methanol crossover effects are two most important barriers that dramatically decrease the electrochemical activity, powder density and faradaic efficiency in direct methanol fuel cells (DMFCs) ,. At present, Pt‐based catalysts are the most common electrode materials for DMFCs, and Pt has become the main bottleneck for widely practical application of the DMFCs due to its high cost and scarcity ,. Therefore, it is urgent to develop an alternative catalyst replacing expensive Pt for ORR with much cheaper price, higher ORR activities, and better methanol‐tolerance ability ,.…”
Section: Introductionmentioning
confidence: 99%